Repopulation dynamics of single haematopoietic stem cells in mouse transplantation experiments: Importance of stem cell composition in competitor cells. (7th April 2016) - Ema, Hideo; Uchinomiya, Kouki; Morita, Yohei; Suda, Toshio; Iwasa, Yoh
Abstract: The transplantation of blood tissues from bone marrow into a lethally irradiated animal is an experimental procedure that is used to study how the blood system is reconstituted by haematopoietic stem cells (HSC). In a competitive repopulation experiment, a lethally irradiated mouse was transplanted with a single HSC as a test cell together with a number of bone marrow cells as competitor cells, and the fraction of the test cell progeny (percentage of chimerism) was traced over time. In this paper, we studied the stem cell kinetics in this experimental procedure. The balance between symmetric self-renewal and differentiation divisions in HSC determined the number of cells which HSC produce and the length of time for which HSC live after transplantation. The percentage of chimerism depended on the type of test cell (long-, intermediate-, or short-term HSC), as well as the type and number of HSC included in competitor cells. We next examined two alternative HSC differentiation models, one-step and multi-step differentiation models. Although these models differed in blood cell production, the percentage of chimerism appeared very similar. We also estimated the numbers of different types of HSC in competitor cells. Based on these results, we concluded that the experimental results inevitably include stochasticity with regard to the number and the type of HSC in competitor cells, and that, in order to detect different types of HSC, an appropriate number of competitor cells needs to be used in transplantation experiments. Highlights: We study a mathematical model for competitive repopulation experiment of HSCs. The test cell type and the composition of competitor cells determine the kinetics. One-step differentiation and multistep differentiation give very similar kinetics. Experimental results inevitably include stochasticity with the HSC in competitor. Detecting different types of HSC, an appropriate number of competitor cells are needed.